PENGARUH MODIFIKASI STANDAR MAKANAN NON DIET TERHADAP BIAYA MAKAN YANG TERBUANG PADA PASIEN GERIATRI KELAS III DI RSUP dr. SOERADJI TIRTONEGORO KLATEN - Mawar Mawar Lestari; Friska Citra Agustia; Dika Betaditya (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2020)
THE EFFECT OF NON-DIET FOOD STANDARDS MODIFICATION ON WASTED FOOD COSTS IN CLASS III GERIATRIC PATIENTS AT RSUP dr. SOERADJI TIRTONEGORO KLATEN ABSTRACT Background: Decreasing food intake in geriatric patients due to physical and psychological conditions has an impact on the high percentage of food plate waste and wasted food costs. This study aims to determine the effect of non-diet food standards modification on the cost of food wasted on class III geriatric patients at RSUP dr. Soeradji Tirtonegoro Klaten. Methods: This experimental study used a post test only with control group design. The sample consisted of 34 people divided into 2 groups, the treatment group that received food standard modification and the control group that received food according to hospital standards. The food plate waste of each group was observed for 2 days using the Comstock visual estimation method. Wasted food costs were calculated by multiplying the percentage of food plate waste per menu item with food prices. The effect of non-diet food standards modification on wasted food costs was analyzed using the Mann Whitney test with a confidence degree of 95% (α = 0.05) Results: The average wasted food cost in the treatment group was Rp 2.806,34 and the control group was Rp 3.443,43. The results of the analysis of the effect of non-diet food standards modification on wasted food cost by the Mann Whitney test showed a p-value of 0.109 (> 0.05) Conclusion: There is no significant effect of non-diet food standards modification on wasted food costs in class III geriatric patients at RSUP dr. Soeradji Tirtonegoro Klaten.